IMPLEMENTASI PERATURAN DAERAH KABUPATEN ROKAN HILIR NOMOR 7 TAHUN 2019 TENTANG IZIN PENANGKARAN SARANG BURUNG WALET TAHUN 2022 - Sari, Diana; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
A swallow's nest breeding permit is a permit given by the regent to every person or entity to carry out swallow's nest breeding activities. Regional Regulation Number 7 of 2019 concerning Permits for Swallow's Nest Breeding was formed in the context of fostering, controlling and controlling swallow's nest breeding activities. However, since the enactment of this regional regulation, not a single swallow's nest breeder in Rokan Hilir Regency has applied for a breeding permit. The aim of this research is to determine the factors that influence the implementation of Rokan Hilir Regency Regional Regulation Number 7 of 2019 concerning Swallow Nest Breeding Permits so that this Regional Regulation does not work. This research uses implementation theory by George Edward III. According to Edward, policy implementation is influenced by four variables, namely communication, resources, disposition and bureaucratic structure. This research uses a research method with a qualitative research approach. This research was conducted in Rimba Melintang District and Bangko District, Rokan Hilir Regency. The research results show that the implementation of Regional Regulation no. 7/2019 has not yet been implemented. The causes are firstly, communication is not yet running, this can be seen from the indicators of transmission, clarity and consistency which have not been effective, resources tend to be good, this can be seen from the indicators of adequate human resources, budget and equipment in the Department of Investment and One Stop Integrated Service in Rokan Hilir Regency, and the disposition that has not been carried out optimally, this can be seen from the commitment of implementors who tend to be lacking in controlling businesses that have violated the rules. And the bureaucratic structure that is already running but not yet optimal can be seen from the SOP indicators that already exist and have been implemented, but from the fragmentation indicators that are not yet running. Keywords : Implementation, Permit for Swallow's Nest Breeding.